Piety and Poisoning in Restoration Plymouth - Marshall, Peter (Studies in church history, 2006)
Can we identify a pre-eminent physical location for the encounter between elite and popular religious mentalities in seventeenth-century England? A once fashionable and almost typological identification of ‘elite’ with the Church, and ‘popular’ with the alehouse, is now qualified or rejected by many historians. But there has been growing scholarly interest in a third, less salubrious, locale: the prison. Here, throughout the century and beyond, convicted felons of usually low social status found themselves the objects of concern and attention from educated ministers, whose declared purpose was to bring them to full and public repentance for their crimes. The transcript of this process is to be found in a particular literary source: the murder pamphlet, at least 350 of which were published in England between 1573 and 1700. The last two decades have witnessed a mini-explosion of murder-pamphlet studies, as historians and literary scholars alike have become aware of the potential of ‘cheap print’ for addressing a range of questions about the culture and politics of early modern England. The social historian James Sharpe has led the way here, in an influential article characterizing penitent declarations from the scaffold in Foucauldian terms, as internalizations of obedience to the state. In a series of studies, Peter Lake has argued that the sensationalist accounts of ‘true crime’ which were the pamphlets’ stock-in-trade also allowed space for the doctrines of providence and predestination, providing Protestant authors with an entry point into the mental world of the people.